INCREASE OF FUNCTIONAL PROPERTIES OF A PIPE STEEL AT THE COMBINED HEAT TREATMENT - O.V. KUDRYAKOV; I.G. POGORELOVA (Вестник Донского государственного технического университета, 2018)
In work the processes of structure formation of a pipe steel under action of various kinds and modes of heat treatment (at furnace or induction heating) are investigated. The efficiency of induction hardening of oil-and-gas pipes from an intercritical interval of temperatures is shown. This mode in a combination with other kinds of heat treatment (normalization, full hardening and tempering) is provided jump of a yield point and especially a cold resisting property of steel (almost on the order at the temperature of test −70°С). At that the steel resistance to some kinds of corrosion trouble, which are featured for the soil of Siberia and Far North, is increased appreciablly.